Three powers in heaven the emergence of theology and the parting of the ways - Fiano, Emanuel (New Haven London Yale University Press, 2023)
"How, when, and why did Christianity and Judaism diverge into separate religions? Emanuel Fiano reinterprets the parting of the ways between Jews and Christians as a split between two intellectual traditions, a split that emerged within the context of ancient debates about Jesus's relationship to God and the world. Fiano explores how Christianity moved away from Judaism through the development of new practices for religious inquiry. By demonstrating that the constitution of communal borders coincided with the elaboration of different methods for producing religious knowledge, the author shows that Christian theological controversies, often thought to teach us nothing beyond the history of dogma, can cast light on the broader religious landscape of late antiquity. Three Powers in Heaven thus marks not only a historical but also a methodological intervention in the study of the parting of the ways and in scholarship on ancient religion."--Dust jacket
Literaturverzeichnis Seite 305-393
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Christianity and other religions -- Judaism -- History -- Early church, ca. 30-600; Church History -- Philosophy -- Primitive and early church, ca. 30-600; Judaism -- History -- Philosophy; Church History -- Primitive and early church, ca. 30-600; Christianity -- History of doctrines; Jewish Christians -- History -- Early church, ca. 30-600; Judaism -- Doctrines; Theology; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity